2013
DOI: 10.4103/2153-3539.114207
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count estimation using the CellaVision DM96 system

Abstract: Introduction:Rapid and accurate determination of platelet count is an important factor in diagnostic medicine. Traditional microscopic methods are labor intensive with variable results and are highly dependent on the individual training. Recent developments in automated peripheral blood differentials using a computerized system have shown many advantages as a viable alternative. The purpose of this paper was to determine the reliability and accuracy of the CellaVision DM 96 system with regards to platelet coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…overall reliability of each of these functions of the DM96 has been assessed by a number of investigators, [1][2][3][4][5][6][7][8] who found the functions to be acceptable for clinical use. However, to our knowledge, no published studies have assessed the reliability of this system in specifically detecting the presence of PLT clumps on peripheral blood smears.…”
mentioning
confidence: 99%
“…overall reliability of each of these functions of the DM96 has been assessed by a number of investigators, [1][2][3][4][5][6][7][8] who found the functions to be acceptable for clinical use. However, to our knowledge, no published studies have assessed the reliability of this system in specifically detecting the presence of PLT clumps on peripheral blood smears.…”
mentioning
confidence: 99%
“…This method is useful to avoid artifacts generating over or underestimation of automated platelet counts and has been reported to be more efficient and more accurate than an alternative microscopic method. This is mainly due to the high-resolution scanning of the defined area of the automated blood smear preparation [8].…”
Section: Microscopic Methodsmentioning
confidence: 99%
“…[ 2 3 4 5 6 7 ] Previous evaluations of these types of systems have shown good correlations with the manual differentiation of normal cells. [ 4 8 9 ]…”
Section: Introductionmentioning
confidence: 99%